Diseño conceptual de un biorreactor para la producción de biomasa de Azotobacter chroococcum a escala banco (2020)
For the preparation of a nitrogen fixing biofertilizer, from the Azotobacter chroococcum strain, it is necessary to use biomass formation under biotechnology systems. The microorganism mentioned above corresponds to the active principle of Azobac, a bioproduct produced by Fundases, a Colombian company which is oriented to the production and development of biosupplies, where currently, they are based on continuous improvement, through a scaling process from its early stages to laboratory-scale until the plant-scale. where it is working for the serial production of biosupplies. A conceptual design of a 7L volume bench-scale bioreactor is necessary, with an effective propagation volume of 5L that allows maintaining the necessary factors to reach a biomass concentration that complies with NTC 5842: 2018 - Colombian technical standard for Biosupplies for agricultural use and Biological Inoculants. - Based on this proposal, an investigation was carried out with Azotobacter chroococcum. Preliminary tests and an approach with the strain were carried out, to define the best configuration that guaranteed a greater biomass production, evaluated between the carbon source factors and the agitation mode. The results of these tests, were the starting point for the realization of microbial growth kinetics, results where it is split to perform technical specifications of the bioreactor of total volume 7 L and effective volume of 5 L, in addition to the sizing of interchangeable structures , among these the mechanical agitation system with Rushton turbine of flat vanes, arrangement of baffles that prevent the generation of vortices, in addition to the monitoring systems of the variables and sensors which perform a follow-up according to the characteristics of the behavior of the biomass.